Application of metal foam heat exchangers for a high-performance liquefied natural gas regasification system. (15th June 2016) - Kim, Dae Yeon; Sung, Tae Hong; Kim, Kyung Chun
Abstract: The intermediate fluid vaporizer has wide applications in the regasification of LNG (liquefied natural gas). The heat exchanger performance is one of the main contributors to the thermodynamic and cost effectiveness of the entire LNG regasification system. Within the paper, the authors discuss a new concept for a compact heat exchanger with a micro-cellular structure medium to minimize volume and mass and to increase thermal efficiency. Numerical calculations have been conducted to design a metal-foam filled plate heat exchanger and a shell-and-tube heat exchanger using published experimental correlations. The geometry of both heat exchangers was optimized using the conditions of thermolators in LNG regasification systems. The heat transfer and pressure drop performance was predicted to compare the heat exchangers. The results show that the metal-foam plate heat exchanger has the best performance at different channel heights and mass flow rates of fluid. In the optimized configurations, the metal-foam plate heat exchanger has a higher heat transfer rate and lower pressure drop than the shell-and-tube heat exchanger as the mass flow rate of natural gas is increased. Highlights: A metal foam heat exchanger is proposed for LNG regasification system. Comparison was made with a shell and tube heat exchanger. Heat transfer and pressure drop characteristics were estimated. The geometry of both heat exchangers is optimized for thermolators. It can be used as a compact and high performance thermolators.